2009
DOI: 10.1021/om9008636
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Terminal Alkynes by Frustrated Lewis Pairs

Abstract: The reactions of frustrated Lewis pairs (FLPs) derived from B(C6F5)3 and the bulky Lewis bases 2,2,6,6-tetramethylpiperidine (TMP), tri-tert-butylphosphine, and lutidine (Lut) with terminal alkynes (acetylene, phenylacetylene, 3-ethynylthiophene) were investigated. The FLPs TMP···B(C6F5)3, t-Bu3P···B(C6F5)3 and Lut···(C6F5)3 reacted with acetylene (HCCH) to yield the apparently thermodynamically more stable E isomers [TMPH][(C6F5)2B−C(C6F5)C(H)B(C6F5)3] (1- E ), t-Bu3PC(H)C(H)B(C6F5)3 (2- E ; 90%), and [t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(133 citation statements)
references
References 48 publications
4
129
0
Order By: Relevance
“…In a related fashion, the reaction of 13 with THF afforded the macrocycle [tBu 2 (17). In a related example, the reaction of Mes 2 PC CBA C H T U N G T R E N N U N G (C 6 F 5 ) 2 with PhC CH gave {[Mes 2 PC CB- (18).…”
Section: Ph][mes 2 Pccba C H T U N G T R E N N U N G (C 6 F 5 ) 3 ] (mentioning
confidence: 99%
See 1 more Smart Citation
“…In a related fashion, the reaction of 13 with THF afforded the macrocycle [tBu 2 (17). In a related example, the reaction of Mes 2 PC CBA C H T U N G T R E N N U N G (C 6 F 5 ) 2 with PhC CH gave {[Mes 2 PC CB- (18).…”
Section: Ph][mes 2 Pccba C H T U N G T R E N N U N G (C 6 F 5 ) 3 ] (mentioning
confidence: 99%
“…[10] In addition, new synthetic routes to such zwitterionic derivatives have been developed from the reactions of sterically encumbered frustrated Lewis pairs (FLPs) with a variety of small molecules including olefins, [11][12][13][14] alkynes, [15][16][17][18][19] CO 2 , [20][21][22] and N 2 O. [23,24] In the case of the reactions of FLPs with alkynes, we have shown that a variety of Lewis bases, including phosphines, [15,17] polyphosphines, [16] amines, thioethers, [18] and pyrroles, [19] will effect addition reactions to give alkenyl-linked zwitterionic products.…”
Section: Introductionmentioning
confidence: 99%
“…It is known from previous publications that FLPs react with terminal alkynes via deprotonative borylation pathway, producing the respective onium alkynylborates 41,42,43,44,45,46 . Indeed, 6 reacts with hex-1-yne giving the respective adduct 31 (Scheme 6).…”
Section: Alkenes Under Hydrogenation Conditionsmentioning
confidence: 99%
“…The same group also showed that some alkenes could undergo C-H bond cleavage using the combination of aluminum compounds and Lewis bases [91]. Terminal alkynes can also be activated by suitable FLPs in a process that is somewhat reminiscent of the copper-assisted deprotonation of alkynes that is at the core of the Sonogashira cross-coupling [25,[92][93]. However, none of these C-H bond cleavage processes could be used for catalytic transformations.…”
Section: C-h Borylation Of Heteroarenes: a Proof Of Conceptmentioning
confidence: 99%